POLA RUANG PERMUKIMAN TRADISIONAL DESA ABABI DI KAWASAN RAWAN BENCANA GUNUNG AGUNG - I Gde Nyoman Ronni Hermawan; I Nyoman Harry Juliarthana (Pranatacara Bhumandala: Jurnal Riset Planologi, 2020)
The traditional settlement of Ababi Village an orientation and hierarchy of spaces to form traditional settlements. the orientation and hierarchy of the hulu teben systems, tri Angga and Tri Mandala. Ababi Village has a settlement pattern located in the Village Center and spreads out following the village road. circulation of internal and external space in disaster mitigation efforts through community movement patterns and the existence of community trust contained in the village awig awig from the existence village protector. Traditions in residents (Krama) trust in environmental conditions in the disaster prone area (KRB) II. This research uses descriptive qualitative and historical methods, through interviews and book literature and research. The spatial pattern results in spatial circulation in an effort to mitigate the great volcano is a resource person who has experience regarding the Agung volcano disaster.